Use of Cow as Draught Power in Some Selected Areas of Bangladesh - Rashid, MU; Rahman, MR; Mammun, ZA (The Agriculturists, 2010)
The study was undertaken to investigate the use of cow as draught power in some selected areas of Bangladesh. Data were collected from 104 purposively sampled respondents from different parts of Tangail, Bogra, Rangamati, Narshindhi, Gopalgang, Gazipur, Chuadanga, Bhola, Faridpur and Barisal district by using interview schedule. It was found that 52 respondents (50 %) used both cow and machinery as source of farm power, while 23 respondents (22.11%) used only animal and 29 respondents (27.88%) used only machinery as the source of farm power. The study showed that top three purposes of using cow were cultivation, milking along with breeding and threshing. The farmers provided 24 suggestions to develop draught cow, among them the most common suggestions were increasing grazing land for draught animal, making animal feed available, launch training programmes for draught animal management and take preventive measures for controlling diseases of cow.